Efektifitas Perlakuan Massage Kepala Dengan Herbal Hair Tonic Terhadap Perspektif Kesegaran Dan Kenyamanan Rambut Dan Kulit Pada Pengunjung Spa - Septiari Nawanksari; Mausa Agrevinna; Manda Yunita Kurniawati (STIKES Columbia Asia Medan, 2026)
Head massage services in the spa industry provide something that people need because many activities cause stress and tension, so this therapy not only functions for physical relaxation, but also contributes to improving mental health and overall well-being. This study aims to analyze the effectiveness of head massage treatment with herbal hair tonic on the perspective of freshness and comfort of hair and skin in spa visitors. Ex post facto research with a quantitative approach. A total of 34 spa visitor respondents were involved in this research as samples. Data was collected through a questionnaire with a 4 Likert scale questionnaire instrument. Data analysis was carried out using regression analysis and SEM analysis. The research results show that head massage treatment with herbal hair tonic has a significant effect on the freshness and comfort of the hair and skin of spa visitors and can increase blood circulation in the head area, which contributes to healthier hair growth and reduces scalp problems such as dandruff and irritation. In addition, the use of natural ingredients in hair tonic not only provides therapeutic benefits, but also creates a deeper relaxation experience for users, which ultimately can increase customer satisfaction and loyalty to spa services.